Green building, materials and civil engineering - Chauhan, Vivek Pratap (SCITUS Academics LLC, 2016)
Green building is the practice of creating structures and using processes that are environmentally responsible and resource-efficient throughout a building's life-cycle from siting to design, construction, operation, maintenance, renovation and deconstruction. This practice expands and complements the classical building design concerns of economy, utility, durability, and comfort. Green building is also known as a sustainable or high performance building. Generally, green homes are healthier, more comfortable, more durable, and more energy efficient and have a much smaller environmental footprint than conventional homes.